P–379 Human platelet lysate improves trophoblast spheroid attachment to primary endometrial epithelial cells from patients with recurrent implantation failure. (6th August 2021) - Nguyen, T T T N; Kwok, Y S S; Russell, S; Librach, C
Abstract: Study question: Could non-autologous platelet lysate (PL) increase attachment of HTR–8 spheroids in vitro to primary endometrial epithelial cells (EECs) from patients with recurrent implantation failure (RIF)? Summary answer: Increased quantity of HTR–8 spheroids attached to primary EECs, isolated from patients with RIF, suggests in vitro treatment with non-autologous PL could improve endometrial receptivity. What is known already: Inadequate endometrial receptivity and thickness are major causes for RIF. Recent studies suggest that platelet-rich plasma (PRP) may improve pregnancy outcomes for RIF and/or thin endometrium (TE) patients. Our previous results show that a commercially sourced and non-autologous human PRP/PL (HPL) promotes EC proliferation in vitro, suggesting that HPL may help to standardize future clinical treatments. In addition to EC proliferation, HPL treatment may improve embryo attachment to primary EECs isolated from patients with a history of RIF. In vitro attachment assays with trophoblast spheroids (embryo model) could help elucidate the effect of HPL on endometrial receptivity in RIF patients. Study design, size, duration: Endometrial tissue was collected from nine RIF patients at the CReATe Fertility Centre, Toronto, Canada (Veritas REB#16580): five with (RIF+TE) and four without a TE (RIF only). Primary EECs were enzymatically isolated and treated with serum-free culture media (SFM) or 1% HPL in SFM for 48 hours before performing the attachment assay. Trophoblast cells (HTR–8/SVneo) were grown in suspension on a rocker to form 70–100 uM spheroids over 24 hours before use in the assay. Participants/materials, setting, methods: Spheroids were fluorescently labelled with calcein-AM for 30 minutes and size-selected to capture spheroids similar in size to a human blastocyst. Spheroids were seeded on top of EEC monolayers and calcein fluorescence was immediately measured by a spectrophotometer. Following the 1-hour incubation, unattached spheroids were aspirated, and fluorescence was measured again. Spheroids were also individually quantified by fluorescent microscopy and ImageJ™ software. The percentage of spheroid attachment was calculated for calcein fluorescence and ImageJ™ quantification. Main results and the role of chance: The HTR–8/SVneo cell line, derived from human first-trimester extravillous trophoblast cells (EVT), has been shown to be a suitable cell line to assess adhesion and invasion in vitro. Trophoblast spheroids generated from this cell line visually resembled a blastocyst and maintained expression of the EVT and implantation biomarkers: GATA3, ITGA5, and LIF. Primary EECs, treated for 48 hours with SFM supplemented with 1% commercially sourced and non-autologous HPL, overall exhibited increased attachment to HTR–8 spheroids. The percentage of spheroid attachment, as measured by fluorescence alone, significantly increase from 47.98% to 64.27% (P < 0.01) of seeded spheroids in RIF+TE EEC cultures, and from 48.12% to 85.77% (P < 0.001) of seeded spheroids in RIF only EEC cultures. Quantification by fluorescent microscopy and ImageJ™ software for individual calcein-stained spheroids, revealed a significant increase in spheroid attachment, from 57.52% to 86.5% (P < 0.01) in RIF+TE EEC cultures, and from 42.58% to 68.90% (P < 0.01) in RIF only EEC cultures. Limitations, reasons for caution: Although there was a positive correlation between calcein fluorescence and spheroid quantity, quantification by fluorescence alone may be unreliable due to the variable numbers of cells in each spheroid. Our data suggest a more precise increase in attachment is detected when quantified by fluorescent microscopy and ImageJ™ software. Wider implications of the findings: We report a method for functional assessment of endometrial receptivity in vitro. HPL appears to promote implantation in RIF patients in a model of embryo attachment. We predict that the observed increase in attachment is due to increased endometrial receptivity gene expression, which will be our next investigative avenue. Trial registration number: N/A